Investigation on Chips Morphology of Machining AISI 4340 under Cryogenic and Cryogenic MQL Conditions - Ahmad, Ahsana Aqilah; A.Ghani, Jaharah; Abdul Rahman, Siti Mariam; Abdul Halim, Nurul Hayati; Abdul Hamid, Adlan Hakimi (International Journal of Integrated Engineering, 2025)
AISI 4340 is a medium carbon low alloy steel that is widely used in heavy industries due to its exceptional material properties such as high hardness and high wear resistance. However, these feature presents significant challenges to the manufacturer thus, necessitating further exploration to improve its machinability. To address this issue, this study aims to analyse the chip morphology, namely chip serration, chip saw-tooth distance, and chip thickness collected during end milling of AISI 4340 under two cutting conditions of cryogenic LN2 cooling and the combination of cryogenic LN2 and Minimum Quantity Lubrication (cryoMQL). By varying the cutting parameter of cutting speeds (Vc), feed rates (fz), axial depths of cut (ap), and radial depths of cut (ae) in these two conditions, the results indicate that the combination between cryogenic and MQL yield better results interm of less chip serration, decrease saw-tooth distance and thinner chips when compared to the standalone coolant technique of cryogenic LN2. The results can be contributed by both cooling and lubricating effect from LN2 and oil from MQL technique that effectively reduce the cutting temperature and limit the temperature built-up at the tooltip. These combinations reduce tool wear, lower friction, and decrease heat generation during cutting thus improving the machinability of AISI4340 especially in critical application.